Is handwriting constrained by phonology? Evidence from Stroop tasks with written responses and Chinese characters - Damian, Markus; Qu, Qingqing (Frontiers in Psychology, 2013)
To what extent is handwritten word production based on phonological codes? A few studies conducted in Western languages have recently provided evidence showing that phonology contributes to the retrieval of graphemic properties in written output tasks. Less is known about how orthographic production works in languages with non-alphabetic scripts such as written Chinese. We report a Stroop study in which Chinese participants wrote the colour of characters on a digital graphic tablet; characters were either neutral, or homophonic to the target (congruent), or homophonic to an alternative (incongruent). Facilitation was found from congruent homophonic distractors, but only when the homophone shared the same tone with the target. This finding suggests a contribution of phonology to written word production. A second experiment served as a control experiment to exclude the possibility that the effect in Experiment 1 had an exclusively semantic locus. Overall, the findings offer new insight into the relative contribution of phonology to handwriting, particularly in non-Western languages.